Approval of the first protease-activated receptor antagonist: Rationale, development, significance, and considerations of a novel anti-platelet agent. Issue 3 (May 2015) - French, Shauna L.; Arthur, Jane F.; Tran, Huyen A.; Hamilton, Justin R.
Abstract: Twenty-three years after the discovery of the first thrombin receptor, now known as protease-activated receptor 1 (PAR1), the first drug targeting this receptor is available for human use. The PAR1 inhibitor, vorapaxar (Zontivity, MSD), was recently approved by the FDA for use in the USA for the prevention of thrombotic cardiovascular events in patients with a history of myocardial infarction or peripheral artery disease. In this review, we detail the rationale, development, as well as the clinical significance and considerations of vorapaxar, the original PAR antagonist and the latest anti-platelet agent in the pharmaco-armoury against arterial thrombosis.